Enhancing mental health pre-service training with the WHO mhGAP Intervention Guide: experiences learned and the way forward - Silje Akselberg Iversen; Brian Ogallo; Myron Belfer; Daniel Fung; Christina W. Hoven; Kenneth Carswell; Norbert Skokauskas (BMC, 2021)
Abstract There is currently a high global demand for mental health professionals, including child and adolescent mental health professionals. In 2020, the World Health Organization (WHO) published "Enhancing mental health pre-service training with the mhGAP-Intervention Guide: experiences and lessons learned" to address the proposition of implementing Mental Health Gap Action Programme Intervention Guide (mhGAP-IG) materials and principles as a component of pre-service training. By integrating the mhGAP-IG within pre-service training, future healthcare providers will acquire theoretical knowledge and early exposure to practical knowledge and will be better prepared for their future work. Examples demonstrate that mhGAP-IG pre-service training can be successfully implemented in diverse settings and in various pre-service training programs. It can be used in small group learning activities and short courses, taught through lectures, used as a clinical tool to teach students (i.e. medical, nursing students) and medical doctors in training. We can enhance pre-service training with the mhGAP-IG and contribute to a learning environment, which nurtures knowledge and skills required to help people with mental health needs.